2015
DOI: 10.3109/14767058.2015.1017813
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of parental prenatal attachment during pregnancy at risk for preterm delivery

Abstract: Hospitalized expecting parents at risk of preterm delivery develop less attachment to the fetus and higher levels of anxiety and depression compared to the physiologic pregnancy group. Maternal antenatal attachment is an independent variable related to the diagnosis of a possible preterm delivery. The promotion of prenatal psychological well-being and attachment for future mothers and fathers may serve to improve maternal health practices, perinatal health and neonatal outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 27 publications
3
62
1
4
Order By: Relevance
“…In 1987, Kemp and Page compared MFA in normal and high-risk pregnancies and found no significant differences between the groups (21). On the other hand, Pisoni et al found that maternal antenatal attachment is significantly lower in a high-risk pregnancy than in a physiologic pregnancy (22). We found that parity, planned pregnancy, and previous spontaneous abortions did not affect maternal-foetal attachment, p > 0.05.…”
Section: Discussionmentioning
confidence: 55%
“…In 1987, Kemp and Page compared MFA in normal and high-risk pregnancies and found no significant differences between the groups (21). On the other hand, Pisoni et al found that maternal antenatal attachment is significantly lower in a high-risk pregnancy than in a physiologic pregnancy (22). We found that parity, planned pregnancy, and previous spontaneous abortions did not affect maternal-foetal attachment, p > 0.05.…”
Section: Discussionmentioning
confidence: 55%
“…The included studies were mainly conducted in the US (10 papers) [80,[84][85][86][87][88][89][90][91][92] and in Europe (nine papers in Italy [93][94][95][96][97][98][99][100][101], four in Sweden [76,[102][103][104], two in Germany [105,106], one in the Netherlands [22], one in France [107], one in England [79], one in Belgium [108], and one in Portugal [75]). Four studies were carried out in Japan [81,[109][110][111], two in Australia [112,113], two in Iran [74,114], two in Turkey [78,115], one in India [116], one in Israel [117], one in Chile [118], one in Brazil [119], and one in Korea [120] (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Considering the 45 studies included in the current review, 31 found a negative association between prenatal attachment and perinatal depression [22,74,75,81,84,86,[89][90][91][92]95,[97][98][99]101,102,[104][105][106][107][108][110][111][112][114][115][116][117][118][119][120], while a positive relation between perinatal depression and some dimensions of antenatal attachment was identified in three studies [94,102,106]. Thirteen studies did not highlight significant associations between these variables [76,[78][79][80]85,87,88,93,96,100,103,109,113].…”
Section: Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Так, исследование итальянских коллег [6], посвя-щенное сравнительной оценке качества антенаталь-ной привязанности (attachment) при физиологиче-ски и патологически протекающей беременности, доказало вполне очевидный факт: высокому риску невынашивания сопутствует состояние депрессии и ситуативной тревоги, причем последняя не зависит от прогноза прерывания беременности и сама по себе снижает формирование привязанности. Тревожно-депрессивный фон при беременности высокого рис-ка существенно тормозит развитие привязанности к малышу у обоих родителей и имеет свои законо-мерности: привязанность у отца напрямую зависит от материнской и очень подвержена негативному влиянию материнской депрессии.…”
Section: стресс рождения недоношенного ребенка и его последствияunclassified